Ketahanan Pangan Rumah Tangga di Kabupaten Jember - Setiawan, Adi; Suciati, Luh Putu; Aji, Joni Murti Mulyo (Universitas Galuh, 2026)
National or regional food security does not necessarily guarantee food security at the household or individual level. Although Jember Regency was classified as a highly food-secure region in 2024 based on Food Security and Vulnerability Atlas (FSVA) data, the reality of household-level food security urgently needs to be addressed. The objective of this research was to analyze household food security conditions based on Engel's Law and Jonsson & Toole's theory. Data from Susenas 2024, analyzed using the Jonsson and Toole method, revealed that the majority of households in Jember still face food vulnerability. Specifically, only about 35.49% (427 households) fell into the food-secure category. Conversely, nearly half, 49.34% (597 households), were in the food- vulnerable category. Additionally, approximately 7.60% (92 households) experienced food scarcity, and 7.77% (94 households) were in a state of food insecurity.